Prevalence and outcomes of peripheral artery disease in a real-world cohort of patients with acute coronary syndrome: insights from the prospective SPUM registry. (3rd October 2022) - Denegri, A; Magnani, G; Kraler, S; Wenzl, F; Raeber, L; Gencer, B; Mach, F; Nanchen, D; Matter, C M; Luescher, T F
Abstract: Background: Despite substantial improvement in secondary preventive therapy, the burden of recurrent cardiovascular (CV) events remains high. Peripheral artery disease (PAD), is a potential marker of increased residual ischemic risk in acute coronary syndrome (ACS) patients suggesting greater net clinical benefit from intensified individualized therapy. Purpose: We aimed to assess the prevalence and cardiovascular (CV) outcomes of peripheral arterial disease (PAD) in 4'787 patients with acute coronary syndromes (ACS) in the Swiss prospective multicenter SPUM study. Methods: PAD was defined according to international guidelines. The composite primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), i.e., stroke, myocardial infarction (MI) and death at 1 year. Adjusted Cox proportional hazards regression models were used to estimate the risk associated with PAD and outcomes. Results: Out of 4'787 ACS patients, 285 patients (6.0%) had PAD. These patients were older (70.1±10.6 vs 63.3±12.4, p<0.001), presented all traditional CV risk factors (all p<0.001) and were more likely to have a complex history of CV disease, such as previous MI (24.3% vs 11.4%, p<0.001), prior percutaneous (32.3% vs 13.8%, p<0.001) or surgical (12.6% vs 3.5%, p<0.001) coronary revascularization. PAD-patients presented also higher levels of inflammatory biomarkers, such as hs-CRP, and GRACE 2.0 score (all p<0.001). At 1 year, patients with PAD had a higher rate of MACCE compared to those presenting without PAD. Rates of the individual components of the primary endpoint and CV-death were all significantly higher in patients with PAD (all p<0.001), except for a numerical increase in MI (5.3% vs 3.3%, p=0.060). This enhanced risk persisted after adjustment for differences in baseline characteristics, with a 53% (Adj. HR 1.53, CI95% 1.14–2.08, p=0.005) increase in MACCE. In spite of high-intensity anti-thrombotic therapy, PAD patients presented the same rate (Adj. HR 1.03, CI95% 0.68–1.54, p=0.901) of major bleeding events at 1 year. Conclusions: Among a real-world cohort of ACS patients, the coexistence of PAD, a very-high CV risk phenotype, is associated with significantly increased rates of MACCE, but no difference in major bleeding events. These observations might help clinicians to further stratify this very-high risk population and to identify patients who may derive the greatest benefit from more intense secondary prevention therapies. Funding Acknowledgement: Type of funding sources: None.